Socio-Economic Conditions Of The Fishing Community Of Tambak Lorok Semarang, North Coastal Waters Of Central Java - Wibowo, Bagus Aris; Sutrisno, Bagus Oktori (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
The fishing community of Tambak Lorok, located on the northern coast of Semarang City, is a coastal community that highly depends on fisheries resources of the Northern Coast of Central Java. This study aims to analyze the socio-economic conditions of fishermen in Tambak Lorok, including demographic characteristics, livelihood patterns, income levels, welfare conditions, and socio-cultural dynamics. The research employed a descriptive qualitative and quantitative approach through field observations, in-depth interviews with fishermen and local stakeholders, and secondary data analysis from relevant institutions and scientific literature. The results indicate that most fishermen operate on a small scale using traditional fishing gear and are highly dependent on weather conditions and fishing seasons, resulting in fluctuating incomes. Limited capital, coastal environmental degradation, tidal flooding, and water pollution significantly affect productivity and economic stability. Socially, the community demonstrates strong social cohesion characterized by mutual cooperation, community solidarity, and the important role of women in supporting household income through fish processing and trading activities. However, low educational attainment and limited access to empowerment programs remain major challenges. This study concludes that the socio-economic condition of Tambak Lorok fishermen remains vulnerable, requiring integrated policy interventions through human resource capacity building, environmentally friendly fishing gear modernization, coastal infrastructure improvement, and the development of alternative livelihoods to enhance fishermen’s welfare and sustainability